Impact of the processes of testicular regression and recrudescence in the prostatic complex of the bat myotis nigricans (Chiroptera: Vespertilionidae) - Beguelini, Mateus R. [UNESP]; Goes, Rejane M. [UNESP]; Rahal, Paula [UNESP]; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastiao R. [UNESP] (Wiley-Blackwell, 2015)
Myotis nigricans is a species of vespertilionid bat, whose males show two periods of total testicular regression during the annual reproductive cycle in the northwest SAo Paulo State, Brazil. Thus, the aim of this study was to investigate the impact of total testicular regression on the prostatic morphophisyology and its regulation. The prostatic complex (PC) of animals from the four periods of the reproductive cycle (active, regressing, regressed, and recrudescence) was analyzed by different histological, morphometric, and immunohistochemical procedures to characterize its variations, analyze its hormonal regulation and evaluate whether the prostate is affected by the processes of testicular regression and recrudescence. The results indicated a decrease in the prostatic parameters from the active to regressed periods, which are related to decreases in the testicular production of testosterone and in the prostatic expression of androgen receptor (AR), estrogen receptor (ER) and aromatase. However, in regressed-recrudescence periods, the prostatic expression of AR, ER and aromatase increased, indicating the reactivation of the PC. Despite this, the PC appears to have a slower reactivation and seems not to follow the testicular recrudescence in morphological and morphometric terms. With these data, we demonstrate that the prostatic physiology is directly affected by total testicular regression and conclude that it is regulated by testosterone and estrogen, via the production of testosterone by the testes, its conversion to dihydrotestosterone by 5-redutase and to estrogen by aromatase, and the activation/deactivation of AR and ER in epithelial cells, which regulate cell expression and proliferation. J. Morphol. 276:721-732, 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: Hormones; Prostate; Regulation; Reproduction; Seasonality